Tolerance to factor VIII in a transgenic mouse expressing human factor VIII cDNA carrying an Arg593 to Cys substitution - Bril, Wendy S.; van Helden, Pauline M. W.; Hausl, Christina; Zuurveld, Marleen G.; Ahmad, Rafi U.; Hollestelle, Martine J.; Reitsma, Pieter H.; Fijnvandraat, Karin; van Lier, Rene A. W.; Schwarz, Hans Peter; Mertens, Koen; Reipert, Birgit M.; Voorberg, Jan (Thrombosis and Haemostasis, 2006)
Inhibitory antibodies develop in approximately 25% of patients with severe hemophilia A following treatment with factor VIII. In E-16KO or E-17KO mice, in which the factor VIII gene has been inactivated by insertion of a neo cassette, inhibitors develop following administration of factor VIII. Here, we describe the generation of transgenic mice expressing human factor VIII-R593C (huFVIII-R593C). Human factor VIII-R593C cDNA under control of a mouse albumin enhancer/promoter was injected into fertilized oocytes. Analysis of transgenic mice revealed that human factor VIII-R593C was expressed in the liver. Transgenic mice were crossed with factor VIII-deficient mice (E-16KO mice). In plasma of E-16KO mice antibodies were detected after five serial intravenous injections of factor VIII, while plasma of huFVIII-R593C/E-16KO mice did not contain detectable levels of antibodies. No antibody secreting cells were observed in either spleen or bone marrow of huFVIII-R593C/E-16KO mice. Also, factor VIII-specific memory B cells were not observed in the spleen of huFVIII-R593C/E-16KO mice. Analysis of T cell responses revealed that splenocytes derived of E-16KO mice secreted IL-10 and IFN-γ following restimulation with factor VIII in vitro. In contrast, no factor VIII-specific T cell responses were observed in huFVIII-R593C/E-16KO mice. These results indicate that huFVIII-R593C/E-16KO mice are tolerant to intravenously administered factor VIII. It is anticipated that this model may prove useful for studying immune responses in the context of factor VIII gene therapy.
Keywords: Transgenic animals; haemophilia A/ B; factor VIII